2014
DOI: 10.1080/14680629.2014.964294
|View full text |Cite
|
Sign up to set email alerts
|

Resilient behaviour of unbound granular materials through repeated load triaxial test: influence of the conditioning stress

Abstract: The present paper reports the results of a laboratory investigation aimed to investigate the resilient behaviour of unbound granular materials (UGMs) for pavement unbound layers under repeated triaxial loading. The first part of research was focused on the effects of stress history, in terms of loading conditioning phase and stress paths, on the resilient response of the investigated UGM. The obtained results highlighted that the samples that experienced several stress paths after an initial stress conditionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Using the UGM specimens with moisture contents below OMC, Arulrajah et al [47][48][49] and Soliman [50] pointed out that the resilient modulus and the resistance of the plastic strain of UGMs under repeated loads declined with the increase in DOS. Zhalehjoo et al [51] and Cerni et al [52] also illustrated that the resilient modulus of UGMs declined with the increase in DOS under varied bulk stresses. Austroads [53,54] describes that the growth of traffic loading and the prediction of extreme weather should be the main requirement of the quality and strength characteristics of UGMs.…”
Section: Effect Of Dos On the Dynamic Response Of Ugmsmentioning
confidence: 93%
“…Using the UGM specimens with moisture contents below OMC, Arulrajah et al [47][48][49] and Soliman [50] pointed out that the resilient modulus and the resistance of the plastic strain of UGMs under repeated loads declined with the increase in DOS. Zhalehjoo et al [51] and Cerni et al [52] also illustrated that the resilient modulus of UGMs declined with the increase in DOS under varied bulk stresses. Austroads [53,54] describes that the growth of traffic loading and the prediction of extreme weather should be the main requirement of the quality and strength characteristics of UGMs.…”
Section: Effect Of Dos On the Dynamic Response Of Ugmsmentioning
confidence: 93%
“…Another previous finding is that under less load cycle, the resilient modulus dominates the permanent deformation [31]. The results of a recent study suggested that axial load, material type, and the maximum particle size are required to be considered for the investigation of confining stress and resilient modulus [32].…”
Section: Introductionmentioning
confidence: 99%
“…e reports from NCHRP (the National Cooperative Highway Research Program) and SHRP (Strategic Highway Research Program) recommend the dynamic modulus test, triaxial static creep test, and triaxial repeated load test to assess the rutting resistance of asphalt mixture [10,11]. G. Cerni put forward a simplified method based on the triaxial repeated load test, which can accurately predict the material characteristics by adjusting the combination of stress and applied stress direction [12]. Park verified the effect of temperature on asphalt mixture by the triaxial repeated load test and predicted the relationship between temperature and rutting by the temperature conversion factor [13].…”
Section: Introductionmentioning
confidence: 99%